Water Disinfection Via Zinc Oxide (ZnO) Nanowires Chemically Fabricated on A Modified Polyurethane Substrate - Alshaybani, Anad M.; Bodowara, Faieza S.; Al Mamlook, Rabia; Abdalrahmn, Zenb Mousa (International Journal of Environment, Engineering and Education, 2024)
Nowadays, water contamination is a big issue due to concerns about health and water scarcity. Unfortunately, most water for human consumption is contaminated with various pathogenic microorganisms that cause water-related diseases. Most traditional chemical and physical disinfectants are energy- and time-intensive and prone to generating harmful disinfection by-products. The recent controversy about waterborne diseases and the safety of commonly used disinfection methods has renewed interest in other forms of disinfection. Low-cost, high-efficiency, and low-energy devices should be developed for potential water disinfection, enabling safe drinking water access. Recently, many researchers have been working on improving the scalability and economics of nanomaterial-based devices to overcome many of the limitations of using traditional anti-microbial agents. Herein, we develop a safe and efficient new nanomaterial decontamination device targeting bacteria in drinking water. Zinc Oxide (ZnO) Nanowires and polyurethane sponges were utilized as affordable and available materials that would lower the cost of the filtration device. The device is based on an electroporation method that applies a low voltage of ~6 V to inactivated bacteria in water. The performance of our device was optimized using different values of voltages, flow rates, microorganism concentrations, and various operation times. By relying on nanotechnology-enabled electroporation principles, this method aims to address the limitations of traditional techniques and offer a feasible solution, especially in areas grappling with contamination issues that lack water treatment infrastructure.